Ground Penetrating Radar Survey of the Lithuanian Part of Medzhybizh Castle - Vietrov, Victor; Bondar, Kseniia M. (Archaeologia Lituana, 2025)
We present the results of recent geophysical and archaeological investigations conducted in Medzhybizh castle located in the Western Ukraine. Architectural and restoration studies that lasted more than 50 years revealed a part of the castle built during the Lithuanian period, in the 14th-15th centuries. Our study is focused on ground penetrating radar (GPR) surveys on the courtyards of the castle including the Lithuanian part, and inside the buildings. The GPR survey was capable of seeing elements of the ancient architecture under a horizon of debris and soil up to 3 m thick. Possible structures of Lithuanian castle were suggested and confirmed by recent archaeological excavations. These are fragments of the Western Wall, stone construction stretching along the façade of the Southern Building, fundament ditch of the inner wall in the Southern Building.